TRANSFORMATION OF SOCIAL NORMS IN THE DEVELOPMENT OF SOCIETY - Berdikulova Surayyo Aslamovna (American Journals Publishing, 2022)
Social transformation expresses the program and project activity of social, economic and other subjects, in which the processes and relations of society are combined with certain norms, standards expressing the properties of the ideal semantic and symbolic environment set by the subjects.
Keywords: transformation, social transformation, development of society, modernization, social process.